Sikap Siswa pada Pembelajaran melalui Teams-Games-Tournament (TGT) - Sitie Chairhany (Al-Liqo: Jurnal Pendidikan Islam, 2022)
This study aims to determine student attitudes in learning mathematics using the Teams-Games-Tournaments (TGT) cooperative at SMK Negeri 1 Tembilahan, Riau. Research respondents consisted of 64 students in class X. A total of 32 students were involved in the experimental group and 32 students for the control group. Mathematical attitudes were measured using 19 questions adapted from Arsaythamby and Rosna Awang Hashim (2009), while 20 questions were used to measure student attitudes using TGT adapted from Slavin (1995). The data were collected three times, namely the Initial Test, Post 1 and Post 2 tests which took place five weeks after the Initial Test and Post 1 Test. Data analysis used mixed between-within subjects ANOVA. The results of this study indicate that mathematical attitudes have an important role in increasing mathematical achievement in TGT cooperative learning. The results of the interviews showed the addition of students' interest and motivation in mathematics in TGT cooperative learning. Meanwhile, the results of the observations show that students and teachers are active during the teaching and learning process using TGT. This can be seen from the interactions between students and teachers who work well together.